The Influence of Competence and Work Environment on Employee Performance with Organizational Commitment as an Interevening Variable - Sofiatun Sofiatun; Tristiana Rijanti (Mandalika Journal of Business and Management Studies, 2025)
This study investigates the influence of competence and work environment on employee performance at the Demak District Health Office, with organizational commitment as a mediating variable. Drawing on quantitative data collected from 51 employees through closed-ended questionnaires, the study employs multiple regression and Sobel tests to evaluate both direct and indirect relationships among variables. The results reveal that competence and work environment significantly and positively influence employee performance. However, neither competence nor work environment has a significant effect on organizational commitment. Moreover, organizational commitment does not significantly influence employee performance and fails to mediate the relationship between competence or work environment and performance. These findings suggest that while employee skills and a supportive work environment directly boost performance, organizational commitment does not play a substantial mediating role. One reason may be that commitment expressed by employees does not translate into active participation or productivity. Factors such as normative attachment and job security may explain high loyalty levels without corresponding performance impacts. The study contributes to human resource management theory by challenging the assumption that organizational commitment always enhances performance. Managerial implications highlight the importance of continuous training to enhance competence, improving work facilities, and designing incentive structures that go beyond fostering loyalty to promote actual performance outcomes. Limitations include a relatively small sample and reliance on self-reported data, which may introduce bias. Future research should explore other mediating factors that link workplace conditions and individual competencies to performance more effectively.